Dampak Kehadiran Minimarket terhadap Pendapatan Kios Kecil di Desa Piru Kecamatan Seram Barat Kabupaten Seram Bagian Barat (SBB) - Sahetapy, Helena; Salakory, Melianus; Manakane, Susan Evelin (Universitas Pattimura, 2026)
This study originates from the rapid growth of modern retail in rural areas, affecting the sustainability of small kiosks in Piru Village, West Seram District, West Seram Regency. The purpose of this research is to analyze the impact of minimarket presence on kiosk income and identify local traders’ adaptation strategies. Using a quantitative descriptive approach through observation, interviews, and documentation involving 12 kiosks and 40 consumers, the results indicate a 61.9% decline in kiosk income and a shift in consumer behavior toward weekly shopping at minimarkets. Traders adapt by diversifying products and extending operational hours, though with limited effect. The study highlights the importance of local economic protection through partnerships between small enterprises and modern retail. Local governments are encouraged to establish fair retail zoning and community-based market integration to sustain socio-economic balance.